Global Commodity Governance - Gale, F. author. aut Link
XVI, 315 p.
Keywords: The Forest and the Marine Stewardship Councils constitute new global governance institutions using voluntary certification and labelling as market incentives to encourage sustainable management. Utilizing a comparative political economic framework, the authors analyse shifting British, Canadian and Australian responses to the stewardship councils.